NEUROLOGICAL INFECTIONS IN THE RETURNING INTERNATIONAL TRAVELER - Han, May H. (2006)
Clinicians may encounter international travelers returning with exotic infections, emerging infectious diseases, or resurgent old-world infections. Many of these infectious diseases can affect the nervous system directly or indirectly. The contemporary neurologist should therefore be cognizant of the clinical manifestations, potential complications, and appropriate management of common travel-related infections. This chapter focuses on five important infections that affect the central nervous system and that may be encountered in returning travelers: Japanese encephalitis, malaria, rabies, dengue, and neurocysticercosis. The clinical manifestations, suggested evaluation, and treatment are discussed for each infection.